Outside Board Human Capital and Early Stage High‐Tech Firm Performance. (30th October 2014) - Vandenbroucke, Elien; Knockaert, Mirjam; Ucbasaran, Deniz
Abstract : Early stage high‐tech firms are confronted with a number of challenges related to the homogeneous and technical nature of the start‐up team. Attracting outside board members can alleviate these challenges and consequently enhance firm performance. Building on team production and human capital theory, we study how outside board human capital affects technological and market performance. Our results, based on a longitudinal panel data set consisting of 562 firm‐year observations in 80 young high‐tech ventures in Belgium, show that outside board‐specific experience, diversity, and tenure are important determinants of firm performance. We discuss implications for research and practice.